Analyzing Factors Affecting Cyberbullying among Students: Its Implication on Social Marketing - Fenfen Nurlita; Asep Rifky Rahman Subagja; Hilman Munawar; Laela Nabilah S; Vika Gustyana Mulyani (Prosiding Industrial Research Workshop and National Seminar, 2018)
Internet development can be advantageous and disadvantageous at the same time. Indonesia, as a country with an increasing number of internet users, has a new problem, called cyberbullying. This study analyzed factors causing someone to perform cyberbullying: such as self-actualization, age, gender, family structure, parental education, and internet frequency. Data were analyzed using binary logistic regression. This study reveals that gender has a significant effect on cyberbullying. Moreover, this study found that self-actualization is also has a substantial impact on cyberbullying. Furthermore, gender is also has a significant effect on some forms of cyberbullying, such as flaming, online harassment, cyberstalking, masquerading, outing and excluding. Internet frequency is also has a substantial impact on online bullying. All findings are used to create the most appropriate social marketing program to prevent cyberbullying from the bullies perspective.